833. POLYGONATUM KINGIANUM: Asparagaceae–Convallariaceae. (June 2016) - Rix, Martyn; Rushforth, Keith
Summary: Polygonatum kingianum Collett & Hemsley, from the mountains of southeast Asia, is illustrated. The variation in the species is discussed, and suggestions for its successful cultivation are given.